Accounting for predator species identity reveals variable relationships between nest predation rate and habitat in a temperate forest songbird. Issue 10 (12th October 2022) - Maag, Nino; Mallord, John W.; Burgess, Malcolm D.; Lüpold, Shannon; Cristinacce, Andrew; Arlettaz, Raphaël; Carlotti, Sandro; Davis, Tony M.; Grendelmeier, Alex; Orsman, Christopher J.; Riess, Michael; Stelbrink, Pablo; et al.
Abstract: Nest predation is the primary cause of nest failure in most ground‐nesting bird species. Investigations of relationships between nest predation rate and habitat usually pool different predator species. However, such relationships likely depend on the specific predator involved, partly because habitat requirements vary among predator species. Pooling may therefore impair our ability to identify conservation‐relevant relationships between nest predation rate and habitat. We investigated predator‐specific nest predation rates in the forest‐dependent, ground‐nesting wood warbler Phylloscopus sibilatrix in relation to forest area and forest edge complexity at two spatial scales and to the composition of the adjacent habitat matrix. We used camera traps at 559 nests to identify nest predators in five study regions across Europe. When analyzing predation data pooled across predator species, nest predation rate was positively related to forest area at the local scale (1000 m around nest), and higher where proportion of grassland in the adjacent habitat matrix was high but arable land low. Analyses by each predator species revealed variable relationships between nest predation rates and habitat. At the local scale, nest predation by most predators was higher where forest area was large. At the landscape scale (10, 000 m around nest), nest predation by buzzards Buteo buteo was high where forest area was small. Predation by pine martens Martes martes was high where edge complexity at the landscape scale was high. Predation by badgers Meles meles was high where the matrix had much grassland but little arable land. Our results suggest that relationships between nest predation rates and habitat can depend on the predator species involved and may differ from analyses disregarding predator identity. Predator‐specific nest predation rates, and their relationships to habitat at different spatial scales, should be considered when assessing the impact of habitat change on avian nesting success. Abstract : Studies about relationships between nest predation rate and habitat usually pool different predator species. However, such relationships likely depend on the specific predator involved, partly because habitat requirements vary among predator species. We show that accounting for predator species identity reveals variable relationships between nest predation rate and habitat in wood warblers.